Analisis Posisi Strategis dan Daya Saing PT Telkom Indonesia Tbk dalam Mempertahankan Dominasi Industri Telekomunikasi - Irfan Apta Maulana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to formulate relevant business strategies for PT Telkom Indonesia Tbk in facing intense competition in the telecommunications sector. A comprehensive strategic management methodology is used, consisting of three analysis phases: entry phase (EFE, IFE, CPM), alignment phase (SWOT, SPACE, BCG, IE, Grand Strategy), and decision-making phase (QSPM). The analysis results show that PT Telkom Indonesia is positioned in the "Aggressive" and "Star" quadrants, indicating that the company holds a very strong market position with potential for further growth. Based on the QSPM matrix, the recommended priority strategy is market penetration with a score of 5.52, which is the most appropriate strategy for the current conditions. This strategy focuses on increasing sales volume, optimizing digital services such as fixed-mobile convergence, and expanding networks to remote areas to broaden market coverage. The implementation of this market penetration strategy is expected to help PT Telkom Indonesia maintain and strengthen its leading position while supporting the ongoing digital transformation in the face of the increasingly competitive telecommunications industry.